Optical Breakdown on Clusters of Gas Nanobubbles in Water; Possible Applications in Laser Ophthalmology - Vladimir A. Babenko; Andrey A. Sychev; Nikolai F. Bunkin (Applied Sciences, 2023)
Here we studied the regimes of optical breakdown in water, stimulated by nanosecond and picosecond laser pulses at a wavelength of 1064 nm. A distinctive feature of our theoretical model, confirmed in experiment, is that in our case the optical breakdown develops on heterogeneous centers-clusters of gas nanobubbles. To the best of our knowledge, this is the first study of the role of clusters of gas nanobubbles in the optical breakdown of liquids that are transparent to pump radiation. In the experiment described in this paper, it was found that when initially degassed water is saturated with dissolved air, the breakdown threshold decreases. A theoretical model describing this phenomenon is suggested. This model includes the development of an electron avalanche inside individual nanobubbles, followed by the stimulated optical coalescence of a nanobubble cluster. According to our estimates, this regime occurs at laser radiation intensities of about 106–107 W/cm2. It is important that at such low intensities the breakdown flash (the basic endpoint of optical breakdown) does not appear due to the deficit of input laser energy. We provide an experimental proof of the coalescence regime, stimulated by a laser pulse in nanosecond range. The experimental threshold of stimulated coalescence is in good agreement with the theoretical estimates. Since the stimulated optical coalescence mode occurs at very low laser intensities, its excitation does not result in mechanical side effects in eye tissues, i.e., a shock wave should not be excited. Note that shock wave always occurs during optical breakdown, which is traditionally excited at intensities of 1012 W/cm2. In our experiment, the generation of a shock wave at such pump intensities was also observed. Since, according to the estimates given in the article, the volume number density of nanobubble clusters in the intraocular fluid can reach 108 cm−3, the excitation of the stimulated optical coalescence mode of nanobubble clusters can be used in ophthalmic surgery, such as laser iridotomy.